Raman scattering in LiNiPO₄ single crystal - Fomin, V.I.; Gnezdilov, V.P.; Kurnosov, V.S.; Peschanskii, A.V.; Yeremenko, A.V.; Schmid, H.; Rivera, J.-P.; Gentil, S. (Физика низких температур, 2002)
The complete Raman spectra of a single crystal of LiNiPO₄ for a wide temperature range are reported. Among the 36 Raman-active modes predicted by group theory, 33 have been detected. The analysis of the spectra in terms of internal modes of the (PO₄)³⁻ group and of external modes is done with success. Besides, the multiphonon Raman scattering is discussed. Low-frequency lines, observed in the antiferromagnetic phase, are assigned to magnon scattering and are discussed briefly.